A novel promotion strategy for microstructure and electrical performance of garnet electrolytes via Li4GeO4 additive. Issue 12 (15th June 2023) - Wang, Ce; Liu, Zhan-Guo; Lin, Pan-Pan; Lu, Fu-Gang; Lin, Jin-Cheng; Shi, Yu-Hao; Xu, Jiu-Jie; Xu, Xiao; Lin, Tie-Song; Dong, Yong-Kang
Abstract: Cubic Li6.4 La3 Zr1.4 Ta0.6 O12 ( c -LLZTO) electrolyte is one of the most promising solid electrolytes. However, it is rather difficult to promote its electrical performance while reducing process parameters. Therefore, Li4 GeO4 is applied as the additive in liquid sintering of LLZTO ceramics in this study. The LLZTO@Li4 GeO4 /Li2 O composite electrolyte sintered at 1180 °C for 3 h performs a significantly promoted microstructure and electrical performance, the ionic conductivity of which reaches 5.77 × 10 −4 S cm −1 at 25 °C. The Li4 GeO4 /Li2 O eutectic phase contributed prominently, in which the high concentration of Li + seaming the LLZTO grains tightly. Meanwhile, Li + conduction in the consecutive conductive pathways constructed by [GeO4 ] groups among the grains was greatly stimulated. With the modification of the grain boundary, an improved garnet electrolytes/Li anode interface performance is produced. The Li/Au|LLZTO@Li4 GeO4 /Li2 O|Au/Li symmetrical cell is able to cycle stably for more than 500 h at the current density of 0.1 mA cm −2 at room temperature.